Diversity of beetles (order: coleoptera) at Gunung Reng, Jeli Kelantan. - Norshabira Noradlan (2017)
Gunung Reng is one of the tourism destination located at Batu Melintang subdistrict, Jeli, in the state of Kelantan, Malaysia. It has beautiful geological landscape with different geomorphological processess, and it has been conserved as natural geological attractions that contribute to benefits to the public and the states of Kelantan. A study on diversity of beetle species has been conducted at Gunung Reng, Jeli, Kelantan from August 2016 to September 2016. The aim of this study was to identify the species richness of Coleoptera in Gunung Reng and to obtain the diversity index of Coleoptera in Gunung Reng. Light trap, pitfall trap and yellow pan trap methods were used to sample the beetle. A total of 51 individuals belonging to 12 species from eight families were recorded in this study. Shannon-Wiener Diversity value is 1.88, and the Margalef’s Richness index value is 2.80. This value shows low beetle diversity and also low species richness of beetle at Gunung Reng, Jeli, Kelantan. The Pielou’s Evenness index value is 0.76 and this value shows that the species of beetles at Gunung Reng, Jeli, Kelantan is well distributed. The diversity of beetle in Gunung Reng, Jeli, Kelantan is considered low. As a conclusion, the diversity of beetle species at Gunung Reng, Jeli, Kelantan is quite low because of the human disturbance of beetles habitat at Gunung Reng, Jeli, Kelantan. A future research on beetle diversity at Gunung Reng, Jeli, Kelantan is recommended because there might be more species that would be collected and identified in the area.